The effect of hydrocortisone on fear information processing and fear extinction - Fay, E (2018)
Introduction: Previous work has revealed that the success of exposure-based therapies in individuals with anxiety disorders can be i) enhanced with pre-treatment glucocorticoid administration and ii) predicted by raised endogenous cortisol levels during treatment. In recent years, computer-based exposure initiatives that minimise costly and time-intensive therapist input whilst providing greater access to treatment have been successfully developed. Given the benefits of these novel approaches, it is plausible that combining treatment ingredients could lead to additional gains. This study aimed to investigate for the first time the potential of hydrocortisone to enhance the efficacy of one-session, computer-based cognitive behavioural therapy (CBT) in participants with high spider fear. It also aimed to determine whether glucocorticoid-enhanced outcomes were predicted by early alterations to the fear bias, which has previously been demonstrated to be a key mediator and predictor of symptomatic improvement in anxious patients. Finally, this study sought to measure endogenous cortisol and cortisone concentrations prior to, during, and after the CBT intervention, in order to determine their predictive value for clinical efficacy at one-month follow-up and change in fear bias on the day after treatment. Methods: In a randomised, placebo-controlled, double-blind study, 33 healthy volunteers with high spider fear were randomised to receive a single dose of hydrocortisone (20mg) or placebo one hour prior to a brief course of computerised and therapist-led exposure-based CBT. Treatment outcome was evaluated using self-report clinical symptom questionnaires, a behavioural approach task, and an implicit evaluation task measuring fear bias. Cortisol and cortisone concentrations were analysed from hair and saliva samples using liquid chromatography tandem mass spectrometry. Cognitive-bias measures were re-evaluated the day following treatment, and all clinical outcome measures were obtained at one-day and one-month follow-up. Results: Compared to placebo, hydrocortisone did not augment the clinical efficacy of one-session CBT. Early changes in the fear bias on the day after treatment were not predictive of clinical symptomatic improvement one-month later in either the hydrocortisone or placebo group. Hydrocortisone administration resulted in a significant acute increase in salivary cortisol and cortisone. Salivary glucocorticoid measurements during treatment and on the morning of treatment did not predict clinical efficacy at one-month. Endogenous baseline hair cortisol did not predict clinical symptomatic improvement. There was a non-significant trend for lower baseline hair cortisone to predict enhanced one-month improvement in the drug group, but not the placebo group. Baseline hair cortisol was not predictive of early changes in the magnitude of fear bias whilst hair cortisone significantly predicted fear bias change across the groups. There was a non-significant trend for this relationship to be stronger in one of the groups, with lower hair cortisone predicting greater fear bias change in the 24 hour period after treatment in the hydrocortisone group, but not in the placebo group. Conclusions: This study provides insight into the interaction between the endogenous glucocorticoid system, exogenous hydrocortisone administration, and the mechanisms and trajectories of clinical symptomatic recovery following a single session of exposure-based CBT. It also highlights the potential for baseline endogenous hair cortisone concentration to be used to distinguish individuals who are likely to respond to therapy from those who are not. An approved understanding of these phenomena, as well as an appreciation of the methodological limitations of this study, will likely be key to enhancing the armoury of psychological and pharmacological tools to more effectively treat anxiety disorders in the future.